2005
DOI: 10.1094/fg-2005-0518-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization Rate and Application Timing Effects on the Yield of Crabgrass

Abstract: Crabgrass (Digitaria species) is a summer annual grass that could provide high quality grazing for ruminant livestock in the mid‐Atlantic region of the United States. However, little is known about managing crabgrass as a forage in this region. This study was designed to evaluate the effect of N fertilizer rate and application timing on the yield of crabgrass. Nine N rates ranging from 0 to 400 lb/acre were applied as a single application at seeding or as a split application, one‐half at seeding and one‐half a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…A 3‐year study in Virginia USA developed N response curves. In one experiment, yield maxima of 4.5, 5.56, and > 4.6 tons/acre in consecutive years at N levels >260 lb/acre were indicated (12), whereas another experiment produced yield maxima of 8.9, 9, and 8.9 tons/acre at respective N levels of 329, 268, and 344 lb/acre (11). The second and third years of those studies occurred in the driest and wettest respective years recorded at that Virginia station, but yield totals there were less affected than in our study.…”
Section: Forage Dry Matter Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3‐year study in Virginia USA developed N response curves. In one experiment, yield maxima of 4.5, 5.56, and > 4.6 tons/acre in consecutive years at N levels >260 lb/acre were indicated (12), whereas another experiment produced yield maxima of 8.9, 9, and 8.9 tons/acre at respective N levels of 329, 268, and 344 lb/acre (11). The second and third years of those studies occurred in the driest and wettest respective years recorded at that Virginia station, but yield totals there were less affected than in our study.…”
Section: Forage Dry Matter Yieldmentioning
confidence: 99%
“…Dalrymple (4) found that N application of the total amount at initiation of growth (single application) usually produced more yield than when half was applied at initiation and half after the first harvest (split application) at any individual harvest, and that total yield was always higher from the single application. Teutsch et al (11) found that applying half of the N at seeding and half after the first harvest increased total production in only one of three years, when compared to applying all of the N at seeding. Furthermore, despite the favorable response of second harvest yields to the split N application, the likelihood of drier conditions in their region following the first harvest led them to suggest that a larger proportion of annual N application should be allocated to the first cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential warm‐season grasses include Caucasian bluestem and crabgrass. Caucasian bluestem performed well in a test of forage‐livestock systems in Virginia, USA (1) and Red River crabgrass has shown promise in Virginia's Southern Piedmont region (6).…”
Section: Introductionmentioning
confidence: 99%
“…Total dry matter production, averaged over years, ranged from 3000 to 9000 lb/acre and increased as N rate increased with maximum dry matter production occurring at 305 lb of N per acre (14). In contrast, the effect of N rate and application timing on forage digestibility and fiber concentration varied.…”
Section: Nitrogen Management For Crabgrassmentioning
confidence: 99%